Rapidly Exacerbating Autoimmune Hemolytic Anemia Together With Marked Cytokine Storm Triggered by Pneumonia Infection: A Case Report - Iwamoto, Yuichiro; Anno, Takatoshi; Koyama, Katsumasa; Shirai, Ryo; Kaneto, Hideaki; Tomoda, Koichi (Frontiers in Immunology, 2020)
Background: Autoimmune hemolytic anemia (AIHA) is caused by hemolysis induced by the reaction of autoantibodies with red blood cells. AIHA is usually classified as either warm antibody or cold antibody-mediated AIHA. In addition, AIHA caused by infection is classified as secondary AIHA. It is well known that alteration of various cytokine levels is closely associated with a variety of disorders such as infectious diseases. In addition, it is known that IL-10/ IL-12 imbalance is an indicator of Th2-dominat conditions and a progressive marker of AIHA. Case presentation: A 82-year-old Japanese man was brought to the emergency room with pneumonia and heart failure. After admission, we started antibiotics therapy. Next day, he had symptoms of jaundice and his total bilirubin level was elevated. Five days after admission, his inflammation markers were further elevated and he had hemolytic anemia. We finally diagnosed him as severe warm-type AIHA associated with pneumoniae infection. Seven days after admission, his severe leucocytosis was further aggravated, and then he suddenly had cardiac arrest and respiratory failure, and finally died of multiple organ failure. Unfortunately, we failed to rescue him from severe AIHA induced by pneumonia infection. Conclusions: Herein, we report a subject with pneumonia-triggered warm-type AIHA together with marked cytokine storm. IL-18 levels were markedly elevated without elevation of IL-12 levels. In addition, IL-10/ IL-12 imbalance was observed. These data suggest that once marked cytokine storm is induced, infection-induced AIHA is exacerbated very rapidly.